2018
DOI: 10.1371/journal.pone.0195680
|View full text |Cite
|
Sign up to set email alerts
|

Hypocomplementemia is associated with worse renal survival in ANCA-positive granulomatosis with polyangiitis and microscopic polyangiitis

Abstract: Recent data suggest the existence of a complement alternative pathway activation in the pathogenesis of antineutrophilic cytoplasmic antibody (ANCA)-associated vasculitis (AAV), a condition that remains poorly understood. This study aims to assess the clinical characteristics and outcomes of granulomatosis with polyangiitis (GPA) and microscopic polyangiitis (MPA) patients with regard to their plasma complement levels at diagnosis. A retrospective monocentric study carried out at Caen University Hospital led t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 28 publications
2
21
0
Order By: Relevance
“…In 25% of the patients with GPA, involvement of the airways can be the only manifestation (15). Levels of C3 and C4 were normal, hypocomplementemia with low C3 and/or C4 levels at GPA or MPA diagnosis may be responsible for worse survival and renal prognosis (16). Platelet to lymphocyte ratio (PLR) as a useful index to estimate the current activity of vasculitis in AAV patients, in our patient was 115, the value >160 is associated with poor prognosis (17).…”
Section: Case Presentationmentioning
confidence: 69%
“…In 25% of the patients with GPA, involvement of the airways can be the only manifestation (15). Levels of C3 and C4 were normal, hypocomplementemia with low C3 and/or C4 levels at GPA or MPA diagnosis may be responsible for worse survival and renal prognosis (16). Platelet to lymphocyte ratio (PLR) as a useful index to estimate the current activity of vasculitis in AAV patients, in our patient was 115, the value >160 is associated with poor prognosis (17).…”
Section: Case Presentationmentioning
confidence: 69%
“…(28)(29) Moreover, a study confirmed the presence of hypocomplementaemia in a small group of patients with worst overall and renal prognosis. (30) Finally, a proteomic analysis of renal tissues from AAV patients with ANCA-negative GN showed larger amounts of C3 and C9 deposition compared with ANCA-positive patients suggesting that ANCA-negative AAV was as a separate disease phenotype, promoted by a specific alteration in the activation of the alternative complement pathway. (31) Since some years, the role of neutrophils in complement activation (both classical and alternative pathways) by expelling neutrophil extracellular traps (NETs) was well characterised.…”
Section: Complement and Glomerular Diseasementioning
confidence: 98%
“…In 2015, Manenti et al reported, in a study that included 46 patients with AAV, that 35% of these individuals had decreased levels of C3 in serum, and this finding was associated with decreased renal survival and the presence of renal thrombotic microangiopathy in the biopsy (39). Recently, a study in 76 AVV patients reported that only 5% had hypocomplementaemia, however, this finding implied worst prognosis with lower overall and renal survival in this subset of individuals (30).…”
Section: Alternative Complement Pathway Profile For Disease Stratificmentioning
confidence: 99%
“…Recent studies have highlighted the role of complement alternative pathway activation in AAV pathogenesis ( 107 ). In a recent randomized trial, Jayne et al have demonstrated that avacopan, an orally administered selective C5a receptor inhibitor was effective in replacing high-dose corticosteroid treatment in AAV ( 108 ).…”
Section: Biomarkers In Psvmentioning
confidence: 99%